Structural features of the human testicular veins walls - Piffer, C. R.; Piffer, M. I.S.; Zorzetto, N. L. (My University, 1988)
The authors observed the microscopic anatomy of both left and right testicular veins, of young and old subjects, as well as the structure of the ostial and parietal venous valves. They verified that the testicular veins walls are of a conjunctive muscular nature, showing at the discharge level, besides the ostial valves, the presence of a functional dispositive that modulates the blood flow into the inferior cava and left renal veins. The authors present a functional interpretation of the architectonic structure of the tissue components from these propelling veins. It is also discussed the causes that lead to the appearance of varices.